Pengaruh Kualitas Pelayanan Islami Terhadap Kepuasan Nasabah Studi Pada Bank Umum Syariah Di Provinsi Lampung - Sefta Kurniawansyah Kurniawansyah; Tulus Suryanto Suryanto; Heni Noviarita Noviarita (Islamic Economics Journal, 2020)
This research aims to analyze the effect of Islamic service quality on customer satisfaction in Islamic banking in Lampung Province. The CARTER dimensions influence on Islamic service quality consists of sharia compliance, assurance, reliability, tangibles, empathy, and responsiveness. In this study, collecting data using a questionnaire was given to 100 samples using regression analysis. The analysis results prove that simultaneously the CARTER dimension has a significant effect on customer satisfaction. In contrast, reliability, sharia compliance, and responsiveness partially significantly affect customer satisfaction in Islamic banking in Lampung Province. Meanwhile, assurance, tangibles, and empathy do not considerably affect customer satisfaction in Islamic banking inLampung Province. Based on the value of Adjusted R Square, the magnitude of the influence of Islamic service quality using the CARTER dimension on customer satisfaction in shariah banking in Lampung Province is 73.8%, so simultaneously, the CARTERdimension affects the quality of Islamic services. Therefore, to maintain and improve this quality, the quality of Islamic banking must be further enhanced through the dimensions of assurance and empathy, namely the bank's ability to give sincere attention and individual or personal care to its customers, as well as commitment and certainty of customer satisfaction, such as showing easyprocedures, good bank reputation, the number of frontliners, security, and facilities and infrastructure provided is even better.